2020
DOI: 10.3390/v12121438
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Epidemiology of the First Wave of SARS-CoV-2 in Italy

Abstract: Italy was one of the first countries to experience a major epidemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), with >1000 cases confirmed by 1 March 2020. However, virus genome sequence data is sparse and there has been only limited investigation of virus transmission across the country. Here, we provide the most extensive study to date of the genomic epidemiology of SARS-CoV-2 in Italy covering the first wave of infection. We generated 191 new full-length genomes, largely sampled from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 31 publications
4
33
0
Order By: Relevance
“…With the exception of this isolated event, there is no evidence of association between any other evolutionary lineage and a single locality. This could be attributed to elevated rates of spread due to freedom of host movement despite social distancing measures established (Di Giallonardo et al, 2020) . Accordingly, lineage representation in Rio Grande do Sul is similar to that found in Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of this isolated event, there is no evidence of association between any other evolutionary lineage and a single locality. This could be attributed to elevated rates of spread due to freedom of host movement despite social distancing measures established (Di Giallonardo et al, 2020) . Accordingly, lineage representation in Rio Grande do Sul is similar to that found in Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…Sequences without a complete date of collection were removed. As per our previous study, cases were grouped according to geographical non-administrative macro areas in North (n=1,195), Central (n= 1,403), and South Italy (n= 3,917) 16 . SARS-CoV-2 lineages were assigned to each sequence using the Pangolin COVID-19 Lineage Assigner tool v2.0.7 (github.com/cov-lineages/pangolin).…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that virus importation associated with travel, followed by local transmission, were key drivers of viral spread during the first wave of SARS-CoV-2 in Italy [ 16 ]. After a year into the pandemic, lockdown restrictions have proven effective in reducing virus transmission and limiting geographic spread [ 17 ], although international travel is still a major source for the introduction of new lineages into Italy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%